Evaluation of PCR for the Identification of Mycoplasma spp. and Mycoplasma genitalium congenital infection in cord blood - Monzavi, Sakineh; Shahhosseiny, Mohammad Hassan; Malek Mohammadi Kalahroudi, Mahsa (Archives of Medical Laboratory Sciences, 2020)
Background: Congenital infections are the most important threat to human fetal health caused by bacterial, viral, and fungal agents. In this study, PCR diagnostic method has been used on umbilical cord samples to diagnose bacterial agents such as Mycoplasmas, especially Mycoplasma genitalium. Materials and Methods: This study was performed on 100 cord blood samples from cesarean section patients. Limit of detection (LOD) and specificity tests of both PCR was performed. DNA samples were extracted by the DNG plus method and amplified by the PCR technique. The optimized PCR product of 715 bp for Mycoplasma spp. and 427 bp for M. genitalium was amplified and observed on 1.5% gel electrophoresis. DNA specificity testing of seven other organisms revealed a 100% specificity of these primers. The detection limit was set at 100 copy / reaction for Mycoplasma.spp and 1000 copy / reaction for M. genitalium. Results: Of the 100 samples examined, 5 samples were positive for Mycoplasma spp, and no positive cases were observed for M. genitalium. Maternal infections can have important consequences on the fetus. Conclusion: Molecular methods such as PCR could be used for rapid identification of important factors in congenital infections, such as mycoplasma, and provide a good prognosis.